The impact of photoionizing feedback in star forming molecular clouds - Nina Sanches Sartorio (2019)
Molecular clouds are imperative to Astronomy as the sites of all known star formation. These clouds are constantly exposed to strong emission of ionizing radiation incoming from the most massive stars. This photoionizing feedback dramatically alters the molecular cloud by ionizing and heating the gas and creating shock fronts, which accelerate and compress gas in the cloud. Thus, this mechanism has important consequences to the chemistry and the dynamics of the environment around the source stars. The goal of this work is to improve our understanding of the role photoionizing feedback from massive stars plays in their own formation and in the dynamics of turbulent gas of molecular clouds. In order to carry out this study, we perform a series of high-resolution radiation hydrodynamics grid simulations. The radiation transfer uses a Monte Carlo scheme, which was coupled to an existing magnetohydrodynamics grid code (AMUN). This new combined code, presented as part of this work, was tested against a number of benchmarks in order to ensure that the coupling between radiation and hydrodynamics was robust. Simulations of turbulent molecular clouds were run with the aim to analyse how the turbulence statistics changed once ionizing feedback was present. We find that this feedback mechanism does not present significant changes to the statistics of the molecular clouds. This, in turn, implies that observational data can be compared with simulations that do not include photoionizing feedback. We also run simulations of massive star formation models with the code CMacIonize. We simulate massive stars accreting through a torus or disk and probe which scenarios the ionizing radiation from the star will lead to a dissipation of the disk and, thereby, a cessation of accretion. We show that ionized regions in this accretion mode take a number of distinct configurations and we establish limiting values for luminosities for which accretion is allowed to proceed for distinct stellar masses and ambient densities. We also find that, if a forming massive star has companions, then it is harder for the photoionizing feedback to lead a stop in accretion and, therefore, that a multiplicity may facilitate massive star formation.